Tumor-like herpes simplex infection in an HIV patient - Lula María Nieto-Benito; Ángel Manuel Rosell-Díaz; Ana Pulido-Pérez; Ricardo Maria Suárez-Fernández (Sociedade Brasileira de Dermatologia, 2021)
Abstract A 56-year-old male, HIV-positive, presented with a 3-day history of multiple indurated erythematous nodules with superficial and well-defined erosions on his right gluteus. Skin biopsy showed ballooning-necrotic keratinocytes and cultures were positive for herpes simplex 2. Genital herpes simplex infection recurrences may not be restricted to the anterior part of the genitalia and clinical presentation in the lumbar area or gluteus must be differentiated from varicella-zoster virus infection. Tumor-like presentation is a very rare manifestation of HSV cutaneous infection. It is important to take this morphological variant into consideration not to delay the diagnosis of a viral infection, especially in an immunosuppressed patient.